Genome-Wide Identification and Expression Analysis of the MADS-Box Gene Family in Sweet Potato [Ipomoea batatas (L.) Lam] - Shao, Zhengwei; He, Minhong; Zeng, Zhipeng; Chen, Yanzhu; Hanna, Amoanimaa-Dede; Zhu, Hongbo (Frontiers in Genetics, 2021)
MADS-box gene, one of the largest transcription factor families in plants, is a class of transcription factors widely present in eukaryotes. It plays an important role in plant growth and development and participates in the growth and development of flowers and fruits. Sweet potato is the seventh most important food crop in the world. Its tuberous roots, stems, and leaves contain a large number of proteins, lipids, carotenoids, anthocyanins, conjugated phenolic acids, and minerals, which have high edible, forage, and medicinal value, and is also an important energy crop. At present, MADS-box genes in sweet potato have rarely been reported, and there has been no study on the genome-wide identification and classification of MADS-box genes in Ipomoea batatas. This study provided the first comprehensive analysis of sweet potato MADS-box genes. We identified 95 MADS-box genes, analyzed the structure and protein of sweet potato MADS-box genes, and categorized them based on phylogenetic analysis with Arabidopsis MADS-box proteins. Chromosomal localization indicated an unequal number of MADS-box genes in all 14 chromosomes except LG3, with more than 10 MADS-box genes located on chromosomes LG7, LG11, and LG15. The MADS domain and core motifs of the sweet potato MADS-box genes were identified by motif analysis. We identified 19 MADS-box genes with collinear relationships and analyzed duplication events. Cis-acting elements, such as light-responsive, auxin-responsive, drought-inducible, and MeJA-responsive elements, were found in the promoter region of the MADS-box genes in sweet potato, which further indicates the basis of MADS-box gene regulation in response to environmental changes and hormones. RNA-seq suggested that sweet potato MADS-box genes exhibit tissue-specific expression patterns, with 34 genes highly expressed in sweet potato flowers and fruits, and 19 genes highly expressed in the tuberous root, pencil root, or fibrous root. qRT-PCR again validated the expression levels of the 10 genes and found that IbMADS1, IbMADS18, IbMADS19, IbMADS79, and IbMADS90 were highly expressed in the tuberous root or fibrous root, and IbMADS18, IbMADS31, and IbMADS83 were highly expressed in the fruit. In this study, the molecular basis of MADS-box genes of sweet potato was analyzed from various angles. The effects of MADS-box genes on the growth and development of sweet potato were investigated, which may provide a certain theoretical basis for molecular breeding of sweet potato.